(untitled) (Malaysian Journal of Learning and Instruction, 2018)
Purpose – The research aimed to examine the construct validity of a scientific-mind measurement model for secondary school students in Bangkok and the factor loading values of scientific-mind indicators. Methodology – Stratified random sampling was used to select a sample of 500 Grade 8 students studying in a Bangkok school district during the 2016 academic year. Testing of scientific-mind measurement was used as the research instrument and construct validity testing of the scientific-mind measurement model utilized second-order confirmatory factor analysis (CFA) was carried out with SPSS AMOS software Version 23. Findings - The testing of the scientific-mind measurement model for secondary school students in Bangkok was consistent with the empirical data. The scientific-mind factors consisted of two indicators, including scientific attitudes and attitudes towards science. Scientific attitudes were comprised of nine indicators. The indicator with the highest factor loading value was creatively working with other people. Attitudes towards science contained four indicators. The indicator with the highest factor loading value was science value awareness. Significance – The results revealed that teachers and educational administrators have the potential to use the study’s scientific-mind factors in their approaches to course development, as well as in designing a manual for learning management. The study’s model can also help in measurement and evaluation of secondary school students’ progress in developing a better scientific mind.